Analisis Peran Polsatwa K-9 Dalam Pidana Narkoba Berdasarkan Perpol 14 Tahun 2018 - Cahyani, Erika; Marpaung, Lintje Anna; B, Erlina (Wajah Hukum, 2023)
Sniffer dogs as police partners can ease the task of investigators because of the expertise of dogs. Dogs have special abilities in their sense of smell, which include being able to detect indications that someone is carrying explosives or narcotics. The research method used in this study is a normative juridical approach so that it only examines the contents of the Indonesian National Police Regulation No. 14 of 2018 concerning changes to the Regulation of the Republic of Indonesia National Police No. 22 of 2010 concerning the organizational structure and work procedures of the regional police, and sources, namely secondary data sources, primary data and tertiary data. In this study, the technique of collecting data obtained from library research and field studies was carried out by means of observation and interviews. The results of this study explain that the role of the K-9 Animal Police Unit in Drug Crimes Based on the Regulation of the Indonesian National Police No. 14 of 2018, sniffer dogs in investigations have a very large role, because they are very helpful for investigating officials to uncover criminal events, but dogs Drug trackers owned by the Ditsamapta Police Unit of the Lampung Police are very limited. The lack of sniffer dogs and handler personnel makes the role of the animal police unit less effective.